The role of miR-128 in cancer development, prevention, drug resistance, and immunotherapy - Budi, Hendrik Setia; Younus, Laith A.; Lafta, Methaq Hadi; Parveen, Sameena; Mohammad, Hawraa Jabbar; Al-qaim, Zahraa Haleem; Jawad, Mohammed Abed; Parra, Rosario Mireya Romero; Mustafa, Yasser Fakri; Alhachami, Firas Rahi; Karampoor, Sajad; Mirzaei, Rasoul (Frontiers in Oncology, 2023)
A growing body of evidence has revealed that microRNA (miRNA) expression is dysregulated in cancer, and they can act as either oncogenes or suppressors under certain conditions. Furthermore, some studies have discovered that miRNAs play a role in cancer cell drug resistance by targeting drug-resistance-related genes or influencing genes involved in cell proliferation, cell cycle, and apoptosis. In this regard, the abnormal expression of miRNA-128 (miR-128) has been found in various human malignancies, and its verified target genes are essential in cancer-related processes, including apoptosis, cell propagation, and differentiation. This review will discuss the functions and processes of miR-128 in multiple cancer types. Furthermore, the possible involvement of miR-128 in cancer drug resistance and tumor immunotherapeutic will be addressed.